The gonzo journalism of Elena Garro - Anticona Alegre, Angie Jennifer (2024)
In gonzo journalism, the reporter or journalist becomes the central axis of the facts, since their subjectivity becomes highly relevant in the narrative. That was precisely what the Mexican journalist and writer Elena Garro did when she lived with the inmates of the Women's Orientation House. Her purpose was to find out firsthand how they lived and find out how they were treated by the reformatory authorities. To fulfill these purposes, she Garro pretended to be a thief, because that way her entry to that place would be easier and no one would suspect her true intentions. The objective of this study is to analyze the journalistic report Mujeres perdidas. Reformatorio de Señoritas, published for the first time in the magazine Así in 1941, republished by Gonzo police journalism retro 01. of Producciones El salario del miedo in 2014 and later published on the Metropolis Fiction website in 2017. This research has a descriptive level, qualitative and not experimental. The content analysis technique is used and its instrument is the analysis matrix. The population is equal to the sample: a journalistic report by Elena Garro.